Direct observation of leakage currents in a metal–insulator–metal capacitor using in situ transmission electron microscopy. (28th August 2018) - Kim, Kangsik; Kim, Jung Hwa; Park, Bo-Eun; Kim, Hyungjun; Lee, Zonghoon
Abstract: With the acceleration of the scaling down of integrated circuits, it has become very challenging to fabricate a metal–insulator–metal (MIM) capacitor with a high capacitance density and low leakage current for nanoscale dynamic random access memory. Yttria-stabilized-zirconia (YSZ) thin films, one of the insulators in the constitution of MIM capacitors, have been reported to have various crystal structures from the monoclinic phase to the cubic phase according to different Y doping levels. The electrical characteristics depend on the crystal structure of the YSZ thin film. Here, we report the local crystallization of YSZ thin films via Joule heating and the leakage current induced during in situ transmission electron microscopy biasing tests. We studied the crystallization process and the increase in the leakage current using experimental and simulation results. It is important to understand the relationship between the crystallinity and electrical properties of YSZ thin films in MIM capacitors.